2016
DOI: 10.1158/0008-5472.can-15-2391
|View full text |Cite|
|
Sign up to set email alerts
|

Jak1–STAT3 Signals Are Essential Effectors of the USP6/TRE17 Oncogene in Tumorigenesis

Abstract: Bone and soft tissue tumors are relatively poorly understood, hampering the development of effective therapies. Here we report a critical effector pathway for the ubiquitin-specific protease 6(USP6)/TRE17, which is overexpressed upon chromosome translation in various human tumors, including aneurysmal bone cyst and the related benign lesion nodular fasciitis. Ectopic expression of USP6 is known to drive formation of tumors which recapitulate key features of ABC and NF, however, the identity of USP6's relevant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…USP6 functions in remodeling of the cytoskeleton and extracellular matrix, inflammatory response, cell signaling, cellular trafficking, and protein turnover, 23,27,[36][37][38][39][40][41][42][43][44] but its specific role in tumorigenesis is not entirely clear. More recently, Quick et al 45 reported that Jak1-STAT3 signaling has an essential role in USP6-related tumorigenesis, while Madan et al 46 suggested a role for Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…USP6 functions in remodeling of the cytoskeleton and extracellular matrix, inflammatory response, cell signaling, cellular trafficking, and protein turnover, 23,27,[36][37][38][39][40][41][42][43][44] but its specific role in tumorigenesis is not entirely clear. More recently, Quick et al 45 reported that Jak1-STAT3 signaling has an essential role in USP6-related tumorigenesis, while Madan et al 46 suggested a role for Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studies identifying the downstream effectors of USP6 will improve our knowledge of and ability to cure these diseases. Actually, two novel genes, the Frizzled and JAK1 genes, were recently identified as USP6 substrates (20,21). Using a DUB library, we identified the transcription factor c-Jun as a novel substrate of USP6.…”
Section: Discussionmentioning
confidence: 99%
“…Data sources and preprocessing. The three data sets (GSE52252, GSE78991, and GSE18229) used in this study were downloaded from GEO (http://www.ncbi.nlm.nih.gov/geo/) (21,(32)(33)(34). Differentially expressed (DE) genes were identified and compared among 9 nodular fasciitis tumors with USP6 translocation in data set GSE78991 and 27 other tumors in data set GSE52252.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on the cellular role and targets of USP6 are sparse, although it has been suggested to deubiquitylate Frizzled and promote Wnt signalling (18), and to deubiquitylate Jak1 causing activation of the STAT3 signalling pathway (19). USP6 has also been demonstrated to regulate the stability of the c-Jun transcription factor (20), and high USP6 protein expression has been observed in bone and soft tissue tumours (21).…”
Section: Discussionmentioning
confidence: 99%